2017
DOI: 10.2500/ajra.2017.31.4472
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regulatory T Cells in the Regulation of Upper Airway Inflammation

Abstract: Allergic rhinitis (AR) and chronic rhinosinusitis with nasal polyps (CRSwNP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 88 publications
0
16
0
1
Order By: Relevance
“…Moreover, Foxp3 levels in an organism can directly reflect the quantity and functional status of Treg cells [28]. A decrease in the number of Treg cells or the loss of function and abnormalities of the key transcription factor Foxp3 are closely related to the pathogenesis of AR [29]. It was demonstrated that inhibition of Notch signaling specifically promotes Foxp3 expression and upregulates the differentiation of Treg cells, thereby reducing the inflammatory response associated with AR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Foxp3 levels in an organism can directly reflect the quantity and functional status of Treg cells [28]. A decrease in the number of Treg cells or the loss of function and abnormalities of the key transcription factor Foxp3 are closely related to the pathogenesis of AR [29]. It was demonstrated that inhibition of Notch signaling specifically promotes Foxp3 expression and upregulates the differentiation of Treg cells, thereby reducing the inflammatory response associated with AR.…”
Section: Discussionmentioning
confidence: 99%
“…In mice sensitized to ovalbumin, Treg cells inhibited allergen-specific IgE responses and affected allergen-specific Th2 cell priming both in terms of proliferative responses and cytokine secretion 10 . In contrast, the depletion of Treg cells during the sensitization phase of allergy development resulted in a dramatic exacerbation of allergic inflammation 11 . In patients with AR, circulating Treg cell numbers in the peripheral blood of patients were either lower than, or equivalent to, those in control patients 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha planteado también que la disminución de las células T reguladoras se relacionaría con la imposibilidad de suprimir el estado inflamatorio, sin embargo, los resultados de los estudios son controversiales, no existiendo actualmente una explicación satisfactoria de las diferencias en los hallazgos 46 .…”
Section: B) Rol Del Sistema Inmune Adaptativounclassified